Affordances Platform and Strategy Game Content Creator on Tiktok @Eanis - Habib AL Anshor; Aghnia Dian Lestari (Asian Journal of Management Analytics, 2026)
Creators have leveraged features of the platform to become highly visible and engaged audience on TikTok but dedication to investigating this practice is still lacked. This qualitative case study focuses on content strategies and platform affordances (especially captions and hashtags) of the Tik Tok profile @eanis, an extraction shooter game content creator. This study aims to identify content strategies, describe how captions and hashtags are used, and understand how creators and audiences interpret these practices by shaping visibility and engagement. Data were collected through in-depth interviews with the main informant and four supporting informants, observation of posts, and literature review. The results show that @eanis's strategy continues to follow trends, especially among extraction shooter players, and that consistency in posting is the basis for establishing the channel's identity.